GAMBARAN TINGKAT KESADARAN KEDISIPLINAN SISWA SMP NEGERI 4 CIPEUNDEUY - Peti Pitriani; Heris Hendriana; Ecep Supriatna (IKIP Siliwangi, 2020)
Discipline is a condition in which all students understand and are aware of compliance with the rules in the school, as the technology of the student's behavior towards school rules begins to shift to a decrease in student awareness of obeying school rules. This research aims to find out the picture of students' awareness of discipline at SMP Negeri 4 Cipeundeuy. The approach used in this study is a qualitative approach with descriptive methods and types of phenomenological research. The data collection technique used is interview. The results of the study revealed that the low awareness of the school rules is because students can not control themselves against the negative influence of the surrounding environment among others; friendship with an environment that is not already in school, students feel that clothes that comply with the school rules are considered incompatible with their character/ geeky, home environment that is not conducive because of parental quarrels that make students fight also in school. Keywords: : Student awareness, Discipline.